Dendritic Phosphorescent Probes for Oxygen Imaging in Biological Systems - Lebedev, Artem Y. (2009)
Oxygen levels in biological systems can be measured by the phosphorescence quenching method using probes with controllable quenching parameters and defined biodistributions. We describe a general approach to the construction of phosphorescent nanosensors with tunable spectral characteristics, variable degrees of quenching, and a high selectivity for oxygen. The probes are based on bright phosphorescent Pt and Pd complexes of porphyrins and symmetrically π-extended porphyrins (tetrabenzoporphyrins and tetranaphthoporphyrins). π-Extension of the core macrocycle allows tuning of the spectral parameters of the probes in order to meet the requirements of a particular imaging application (e.g., oxygen tomography versus planar microscopic imaging). Metalloporphyrins are encapsulated into poly(arylglycine) dendrimers, which fold in aqueous environments and create diffusion barriers for oxygen, making it possible to regulate the sensitivity and the dynamic range of the method. The periphery of the dendrimers is modified with poly(ethylene glycol) residues, which enhance the probe’s solubility, diminish toxicity, and help prevent interactions of the probes with the biological environment. The probe’s parameters were measured under physiological conditions and shown to be unaffected by the presence of biomacromolecules. The performance of the probes was demonstrated in applications, including in vivo microscopy of vascular pO(2) in the rat brain.